A state-of-the-art review and prospect of gas hydrate reservoir drilling techniques - Wei, Na; Pei, Jun; Zhao, Jinzhou; Zhang, Liehui; Zhou, Shouwei; Luo, Pingya; Li, Haitao; Wu, Jiang (Frontiers in Earth Science, 2022)
Securing energy means grasping the key link in the national development and security strategy. Under the goals of carbon peak and carbon neutrality, the overall tendency of energy development is to increase the proportion of natural gas while stabilizing oil consumption, and the global primary energy is entering the era of natural gas. Gas hydrate in deep seabed shallow strata and extremely cold permafrost regions has piqued the interest of researchers due to its abundant resources, widespread distribution, and high energy density. Although the drilling of hydrate wells is still fraught with unknowns and challenges due to the technological barriers between countries, complex on-site working conditions, and unique physical chemical properties, accumulation forms, and occurrence characteristics of gas hydrate, more than ten successful trial productions around the world have opened the door of hope for the development of this potentially new energy. The gas hydrate reservoir drilling technique is the frontier and hotspot of scientific and technological innovation and competitiveness around the globe today, reflecting the level of oil and gas technical advancement. At the national level, it possesses strategic and revolutionary features. Innovative drilling techniques, scientific well location layout, appropriate wellbore structure and well trajectory design, efficient drilling fluid, qualified drilling and completion equipment, and successful pressure-temperature preserved coring may all provide a strong guarantee for the successful completion of gas hydrate wells. This review comprehensively reviews the drilling techniques and engineering measures that can be used to develop gas hydrate. It focuses on the research advancement of important hydrate drilling technologies and the enlightening significance of these developments in the application of hydrate drilling. This work will deliver valuable experience as well as comprehensive scientific information for gas hydrate exploration and drilling.